Penerimaan Sakramen Baptis bagi Bayi dari Pasutri yang Mengalami Halangan Perkawinan Katolik - Lumen Christian, Stefanus (Institutum Theologicum Ioannis Mariae Vianney Surabayanum, 2023)
Sacraments are signs and means of God's saving presence. The sacrament of Baptism is one of them so that baptism also shows the salvation that comes from God. Everyone can receive the Sacramentof Baptism. This is because the Sacrament of Baptism makes everyone, who receives it, a member of the Church. In fact, they also receive an eternal seal that makes them commissioned to proclaim God's salvation. Receiving the Sacrament of Baptism means being born again to become children of God. In the Baptism ceremony, water is the main material because water is a means of cleansing. In fact, water has a great role for human life. The word